Role of sleep disturbances in occupational accidents among women - Shadi Amid Hägg; Kjell Torén; Eva Lindberg (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: This population-based cohort study was performed to assess the association between sleep disturbances and the risk of occupational accidents among women. METHODS: Data were collected by questionnaires on two different occasions (2000 and 2010) and data on work injuries were also collected from Swedish government records (ISA). Insomnia symptoms were defined as having severe or very severe problems with (i) difficulty initiating sleep, (ii) difficulty maintaining sleep, or (iii) early morning awakening. Symptom of obstructive sleep apnea syndrome (OSAS) was defined as reporting both snoring and daytime sleepiness. Working-age respondents (20-67 years of age) who responded to both baseline and follow-up questionnaires and had worked for part or all of the 10-year follow-up period (N=4320) were included in the study. RESULTS: Of the subjects responding to the questionnaire, 12.2% reported ≥1 accident and 6.3% reported an accident requiring sick leave in the government register. Blue-collar workers and night and shift work were more common in the group with occupational accidents. Subjects with insomnia symptoms both at baseline and follow-up (persistent insomnia symptoms) ran a higher risk of being involved in an self-reported occupational accident [adjusted OR (OR_adj) 1.5, 95% confidence interval (95% CI) 1.2-2.0] after adjusting for age, body mass index, smoking, alcohol dependency, white- or blue-collar worker, years at work, night work, and physical activity. Persistent insomnia symptoms did not reach statistical significance as an independent predictor of register-reported occupational accident with sick leave (OR_adj 1.4, 95% CI 0.99-2.1). No significant association was found between symptoms of OSAS and self-reported or register-based occupational accidents. CONCLUSIONS: Persistent insomnia symptoms were associated with an increased risk of self-reported occupational accidents, while no significant association was found with occupational accidents with sick leave reported to government register.